2004
DOI: 10.1177/230949900401200111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunohistochemical Characteristics of Benign Giant Cell Tumour of Bone with Pulmonary Metastases: Case Series

Abstract: Three of the 5 primary tumours had a benign clinical pattern and immunohistochemistry. Two of the 5 patients died of pulmonary metastases, which had an aggressive clinical pattern and a high prevalence of positive cells in Ki-67. Examination of Ki-67 should be carried out for aggressive type of giant cell tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
0
25
0
4
Order By: Relevance
“…11 Benign GCT of bone with pulmonary metastasis occurs most frequently in recurrent cases; these recurrent tumours have the potential to develop malignant biological behavior. [8][9][10] Study by Viswanathan S shows that, out of 24 tumors metastasized, 13 developed recurrence prior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Benign GCT of bone with pulmonary metastasis occurs most frequently in recurrent cases; these recurrent tumours have the potential to develop malignant biological behavior. [8][9][10] Study by Viswanathan S shows that, out of 24 tumors metastasized, 13 developed recurrence prior.…”
Section: Discussionmentioning
confidence: 99%
“…Although distant metastasis from GCT is known to be rare, cases were reported in locations like bone, muscle, lymph node, breast, penis, skin, brain, adrenal, GIT, kidney with lung being the common site having an incidence between 1-9%. [2][3][4][5][6][7][8][9][10][11][12]15 Clinical data from literature shows that age of the patients ranges between 15-61 with mean age being 31.8 with a male predominance. 16 Risk factors for pulmonary metastasis include primary site, locally aggressive tumors, multiple recurrences and modality of treatment of primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who experienced at least one local recurrence were reported to be more likely to develop lung metastases than those who had no local recurrence. Patients with positive cells for Ki-67 in immunohistochemistry in stage III giant cell tumours seemed to have a higher prevalence of lung metastases [16].…”
mentioning
confidence: 99%
“…7,8 Previous studies have not found any significant difference in the proliferation of neoplastic cells between primary and recurrent GCT. 4,9,10 The present study was undertaken to evaluate whether delineation of reactive and neoplastic component of GCT using immunohistochemistry can help in deriving histopathological performance indicators which differ in primary and recurrent GCT. Nuclear morphometry of immunostained slides by image analysis was used for more accurate measurement and to assess the utility of this approach.…”
Section: Introductionmentioning
confidence: 99%